Structural Design of the AZ Hotel in Al-Hijri / Dora - Ihmedat, Shrouq; Fanoun, Mohammed (جامعة بوليتكنك فلسطين - مباني, 2023)
The main idea of the project revolves around the structural design of AZ Hotel, the structural design is one of the most important designs subsequent to the architectural design process, as the process of distributing columns and studying the behavior of the building under the influence of vertical and horizontal loads and choosing The best type of knots, walls and foundations and following the best methods and solutions from an economic point of view is the main objective of this project. AZ Hotel is a proposed hotel to be built in the mountainous village of Al-Hijri in the town of Dura. Architecturally, this project is characterized by the presence of setbacks that led to a difference in floor space, in addition to differences in levels. The project consists of 6 floors in addition to two basement floors, the second basement floor is a Parking and the first basement floor is for various services, and the total area is about 11128m2 . After completion of the project, we expect to be able to provide structural design of all the structural elements of the project accordance to the requirements of the code (ACI-318-11, ACI318-08, Jordanian code).
CD, no of pages 99, مباني 6/2023
Keywords: Structural Designs